Brucella spp. in aquatic mammals of Brazil: serological, molecular, histopathological and immunohistochemical investigation - Sarmiento, Angelica Maria Sanchez (2018)
Aquatic mammals are sentinels of zoonotic pathogens that may be a threat to species conservation, to humans and domestic animals. Brucella genus is responsible for brucellosis, one of the main widespread zoonosis. In aquatic mammals, Brucella spp. was firstly described in 1994 and currently there are two recognized species infecting that group: B. ceti and B. pinnipedialis. In cetaceans, Brucella spp. has been linked to asymptomatic infection, acute or chronic disease and several pathological processes which may lead to stranding and/or death. In pinnipeds, pathogenicity of Brucella spp. is still unclear. Data about Brucella spp. in aquatic mammals in South Atlantic Ocean particularly in Brazil is limited, with a significant knowledge gap despite the rich diversity of this group. In this research, we investigated exposure to and/or infection by Brucella spp. by serological, molecular, histopathological, immunohistochemical and microbiological methods in samples of aquatic mammals of Brazil kept at the Marine Mammal Tissue Bank, Department of Pathology, School of Veterinary Medicine and Animal Sciences, University of São Paulo, Brazil. Sera from 63 cetaceans [families Iniidae (n=37), Delphinidae and Kogiidae (n=26)], 35 pinnipeds (Southern elephant Seals, Mirounga leonina), and 21 West Indian manatees (Trichechus manatus) were tested via the Rose Bengal Test, a commercial competitive enzyme-linked immunosorbent assay (c-ELISA) and the serum agglutination test (SAT; selected c-ELISA positives) to detect Brucella spp. antibodies. In addition, DNA from selected samples of 124 cetaceans, 4 pinnipeds and 1 manatee were analyzed by conventional PCR and/or real-time PCR (qPCR) targeting the genus Brucella spp. Culture, histopathology and immunohistochemistry (IHC) were performed in samples from exposed or infected individuals (serology and/or conventional PCR/qPCR positives; n=13). Antibodies against Brucella spp. were detected in 3/35 (8.6%) of the M. leonina tested while Iniidae and Kogiidae cetaceans and manatees were negative. Brucella spp. DNA was detected in 4/124 (3.2%) of the cetaceans tested by conventional PCR/qPCR: one Clymene dolphin (Stenella clymene) with acute brucellosis, positive by serology and IHC; and three other individuals without available sera: one asymptomatic Franciscana (Pontoporia blainvillei), positive by qPCR and IHC; one case of chronic brucellosis in a Spinner dolphin (Stenella longirostris) presenting fibrinosuppurative atlanto-occipital osteoarthritis with abscess formation, positive by qPCR and by IHC; one Guiana dolphin (Sotalia guianensis), positive by conventional PCR/qPCR and by IHC and previously diagnosed with cetacean morbillivirus. Despite negative PCR amplification, Brucella-type lesions were found in one S. clymene and one pigmy killer whale (Feresa attenuata), both positive by serology and by IHC. Positive serology and/or IHC suggested exposure and/or Brucella-infection in three short-finned pilot whale (Globicephala macrorhynchus), two melon-headed whale (Peponocephala electra), a bottlenose dolphin (Tursiops truncatus) and a S. clymene. Main part of the Brucella spp. exposed or infected cetaceans came from State of Ceará, Northeastern Brazil. Culture was not successful, hampering strains classification. All the pinnipeds and the manatees tested by PCR were negative. Opportunistic screening of Leptospira spp. exposure via the microscopic agglutination test on all sera samples used for the Brucella spp. screening gave negative results. In conclusion, we found Brucella spp. exposure, asymptomatic infection, as well as cases of acute and chronic brucellosis and coinfection by Brucella spp. and other pathogens. To our knowledge, this research is the first long-term survey of Brucella spp. in aquatic mammals in South America, widening the hosts and the geographic range of this agent and contributing to the understanding of pathological and epidemiological aspects of its infection. Further research is needed to fully characterize the strains involved, evaluate their public health relevance and the possible occurrence and impacts in other species of aquatic mammals in Brazil.